Penyusunan Zonasi Kawasan Pertambangan Di Kabupaten Magetan Berdasarkan Aplikasi Sistem Informasi Geografis Dengan Metode Pertampalan - Yazid Fanani; Fajar Rizki Widiatmoko; Salahudin Al Fakih; I Wayan Koko Suryawan; Mega Mutiara Sari (Jurusan Teknik Pertambangan, Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2021)
Magetan has resources mineral potential of non-metallic minerals and rocks. The mineral variety is a mineral which relates to the people livelihood because it necessary for infrastructure development. There is no mining area zoning until now and it can be used to optimize the management and utilization of potential resources. In Magetan, mining area zoning was carried out by giving weights and assessments to the determining parameters which was conducted by patch method and it utilized Geographic Information System. So, the result of mining area zoning could be grouped into three zones. They were a zone could be granted a mining permit, a zone could be granted a conditional mining permit and a zone could not be granted a mining permit. Determining parameters for mining area zoning were land height, disaster vulnerability, groundwater, river borders, lakes and irrigation buildings, springs, forests and protected areas, agricultural land and cultivation areas, settlements, cultural heritage, tourism and district strategic areas, and land slope. The result of potential resources identification was carried out by analyzing Magetan geological map which was obtained potential resources, like andesite, pumice breccia, sandstone, siltstone and basalt. The zoning of Magetan mining area is a zone could bne granted a mining permit and the area was 9,914.507 Ha or about 14% in a percentage of the area, a zone could be granted a conditional mining permit covering an area of 20,748.29 Ha or about 30% and a zone unable to be granted a mining permit covering an area of 39,296.08 Ha or about 56% of the total area of Magetan.